Tribological characteristics and film behaviour of polytetrafluoroethylene in jatropha with sodium dodecyl sulphate as surfactant - Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Opia, Anthony Chukwunonso; Veza, Ibham (SAGE Publications Inc., 2024)
In this research, a bio lubricant was developed utilising eco-friendly constituents of jatropha oil, polytetrafluoroethylene (PTFE) and sodium dodecyl benzenesulphonate (SDBS), characterised and tested with four-ball tribometer under ASTM D2783 standard. The tribological performance in terms of friction, wear, load carrying ability and evaluation of the film behaviour on stability and strength was conducted. According to Fourier transform infrared spectroscopy (FT-IR) of the study, the presence of the two additives in base jatropha oil demonstrated good functional groups desired for lubricant lubricity. In comparison to base jatropha under 40 kg and 1200 rpm, blended 1 wt-% PTFE+0.8 wt-% SDBS additives produced an outstanding reduction in coefficient of friction (61.4%) and good load carrying strength among all the samples tested, but commercial shell oil (CSO) outperformed under wear resisting potential. Scanning electron microscopy (SEM) and a 3D surface profilometer were used to examine the rubbed surfaces. Findings indicate that the boundary film on the worn surface was made up of PTFE and SDBS nanoparticles that deposited film elements of sulphur and higher carbon content. The decrease in the percentage of iron (Fe) indicates that tribo-pairs were separated from direct contact under additives usage. According to the research, adding an anti-wear substance to the new formulation could increase wear protection, thus effectively making it comparable with CSO counterpart.